Relationship Between Socia-Economic Status and Parental Education Towards Students Entrepreneurial Interests - Oktarina, Harti; Agung, Eka Adnan (Universitas Negeri Makassar, 2024)
The purpose of this study was to determine (1) how the perception of parental employment status, parental education level, and students' entrepreneurial interest at SMK Jaya Negara Makassar, and (2) whether there is a relationship between parental employment status and parental education level with students' entrepreneurial interest. This study investigated the relationship between descriptive methods and other methods. Questionnaires and instructions were the data collection methods. The research tool was tested on 27 respondents. The analysis prerequisite test consisted of normality and linearity tests, reliability tests using Cronbach alpha, and instrument validity tests using the product moment formula. Hypothesis testing used correlation tests. The results of the study show several things. First, there is a positive and significant correlation between the employment status of students of SMK Jaya Negara Makassar and their desire to become entrepreneurs. Based on the analysis, the correlation coefficient rxy is 0.585 (rxy of 0.585 is greater than rtable 0.367). Second, there is a positive and significant correlation between the level of education of students' parents and their desire to become entrepreneurs. The correlation coefficient rxy is 0.669 (rxy of 0.669> rtable 0.367).